A line planning approach for high-speed railway network with time-varying demand. (October 2021) - Zhao, Shuo; Wu, Runfa; Shi, Feng
Highlights: Optimize line planning for high-speed railway network with time-varying demand. Extend the conventional line plan by introducing estimated starting time. Construct a game-theoretic bi-level programming model for problem formulation. Propose a decomposition searching strategy to solve the model. Abstract: Line planning is a critical issue in railway planning as a connecting link between supply and demand. This paper proposes an approach to optimize line planning problem (LPP) for the high-speed railway (HSR) network to provide higher service level for time-varying demand. A bi-level programming model based on Stackelberg game theory is constructed, incorporating passenger flow assignment into line planning to obtain a cost and customer-oriented line plan which is extended by introducing the "estimated starting time" to obtain time information and evaluate the match degree between the line plan and travel demand. The model is solved under the framework of Simulated Annealing Algorithm (SAA) by a decomposition searching strategy combining the efficiency evaluation of in-line subplans and the whole network line plan to improve the stability of solutions. A case study on a partial HSR network in China is presented, and it demonstrates that the optimized line plan can not only fit the fluctuation of travel demand, but also increase the utilization ratio of the transit capacity.